Organic Electronics: Ultraconformable, Self‐Adhering Surface Electrodes for Measuring Electrical Signals in Plants (Adv. Mater. Technol. 4/2021). Issue 4 (5th April 2021) - Meder, Fabian; Saar, Sirgi; Taccola, Silvia; Filippeschi, Carlo; Mattoli, Virgilio; Mazzolai, Barbara
Abstract : The cover shows a self‐adhering, ultraconformable, organic electrode assembly measuring surface potentials on a Venus flytrap as studied by Fabian Meder, Virgilio Mattoli, Barbara Mazzolai and co‐workers (article number 2001182 ). The electrodes are easy‐to‐apply, light‐weight, and long‐term‐performing. Utilizable to record and bidirectionally stimulate electrophysiological signals in different plant species, the devices are relevant for plant science and plant‐hybrid robotics and ‐sensors.